Retinal nerve fibre layer thinning in patients with clinically isolated optic neuritis and early treatment with interferon-beta - Sühs, Kurt-Wolfram; Diem, Ricarda (PLOS ONE, 2012)
Background Optic neuritis is associated with neurodegeneration leading to chronic impairment of visual functions. Objective This study investigated whether early treatment with interferon beta (IFN-β) slows retinal nerve fibre layer (RNFL) thinning in clinically isolated optic neuritis. Methods Twenty patients with optic neuritis and visual acuity decreased to ≤0.5 (decimal system) were included into this prospective, open-label, parallel group 4-month observation. After methylprednisolone pulse therapy, 10 patients received IFN-β from week 2 onwards. This group was compared to 10 patients free of any disease modifying treatment (DMT). The parameter of interest was change in RNFL thickness assessed at baseline and at weeks 4, 8, and 16. Changes in visual acuity, visual field, and visual evoked potentials (VEPs) served as additional outcome parameters. Results RNFL thinning did not differ between the groups with a mean reduction of 9.80±2.80 µm in IFN-β-treated patients (±SD) vs. 12.44±5.79 µm in patients who did not receive DMT (baseline non-affected eye minus affected eye at week 16; p = 0.67, t-test, 95% confidence interval: −15.77 to 10.48). Parameters of visual function did not show any differences between the groups either. Conclusions In isolated optic neuritis, early IFN-β treatment did not influence RNFL thinning nor had it any effect on recovery of visual functions.
Gesehen am 14.06.2018